2021
DOI: 10.1007/s11277-021-09066-y
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Redundant Discrete Wavelet Transform (ML-RDWT) and Optimal Red Deer Algorithm (ORDA) Centred Approach to Mitigate the Effect of ICI, BER and CIR in a MIMO-OFDM System

Abstract: Nowadays, there is a great demand for ultra-high data rate (UHDR) transmission on most 5 th generation wireless networks. In this concern, the multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) scheme is used on a large scale to achieve UHDR transmission with reduced inter-symbol interference (ISI) and inter-carrier interference (ICI). Discrete wavelet transform-based OFDM (DWT-OFDM) provides better orthogonality due to presence of orthogonal wavelets, which mitigates the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This method obtains a very BER of 2.65 for 14‐dB SNR. Another study reported in Nagarajan and Sophia 23 introduces space time block codes (STBCs) into the MIMO‐OFDM model that can effectively reduce the frequency of selective fading without increasing the BW consumption. The BER obtained by this method was about 1.5 at an SNR of 20 dB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method obtains a very BER of 2.65 for 14‐dB SNR. Another study reported in Nagarajan and Sophia 23 introduces space time block codes (STBCs) into the MIMO‐OFDM model that can effectively reduce the frequency of selective fading without increasing the BW consumption. The BER obtained by this method was about 1.5 at an SNR of 20 dB.…”
Section: Resultsmentioning
confidence: 99%
“…Nagarajan and Sophia 23 define the multilevel RDWT and ORDA strategies for reducing the effects of ICI, BER, and CIR in a MIMO‐OFDM system. In this method, a multilevel RDWT technique was contemplated to enhance the spectral efficiency; thus, the downsampling operation was prevented.…”
Section: Related Workmentioning
confidence: 99%
“…In 2021, Nagarajan and Sophia [24] had suggested multilevel redundant discrete wavelet transform (ML-RDWT) to overcome the effects of down-sampling which degrades the system performance. Further, optimal red deer method (ORDM) is used to optimize the weight to achieve better ICI cancellation.…”
Section: Related Workmentioning
confidence: 99%
“…On the receiver side, the cyclic prefix is neglected and symbols are again converted into the frequency domain using the fast fourier transform (FFT) as shown in Eq. (3).…”
Section: Mimo-ofdm System Modelmentioning
confidence: 99%
“…MIMO is the reliable approach that can handle the increasing wireless data traffic of the future generation of a wireless communication network [2]. Moreover, the connection of multiple transmitters and receivers at both ends of the MIMO system is used to increase the channel capacity [3,4]. OFDM is the essential approach for the mobile communication network because of its higher spectral efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%